Influence of Service Quality Servicescape and Word of Mouth on the Decision to Use Expedition Services JNE City Tebing High With Trust as an Intervening Variable - Bobby Hartanto; Tarisyah Ramadhani (International Journal of Economics (IJEC), 2023)
This study aims to determine the effect of service quality. servicescape and word of mouth on the decision to use JNE expedition services in Tebing Tinggi City with trust as an intervening variable. The effect that we want to know is the direct or indirect effect. The research method used is a quantitative method using the help of software smart pls 3.0. this type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. This study used a sample of 96 respondents. Sampling using probability sampling technique. From the results of the direct influence test. it can be concluded that service quality (X1) and word of mouth (X3) have a significant effect on trust (Z). while servicescape (X2) has no significant effect on trust (Z). Service quality (X1) and trust (Z) have a significant effect on usage decisions (Y). while servicescape (X2) and word of mouth (X3) have no significant influence on usage decisions (Y). The indirect test results show that the quality of service (X1) and word of mouth (X3) affect the decision to use (Y) which is mediated by trust (Z). while the servicescape (X2) has no effect on the decision to use (Y) which is mediated by trust (Z).